Rational design of a triple-type human papillomavirus vaccine by compromising viral-type specificity - Zhihai Li (Nature Portfolio, 2018)
More than 18 human papillomaviruses (HPV) are associated with cervical cancer, and ideally vaccines should protect from all of them. Here, the authors engineer a triple-type, chimeric HPV vaccine, using loop swapping, that elicits robust neutralizing antibody titers in mice and non-human primates.